SUI GENERIS MANAJEMEN APLIKATIF TAHFIDZ AL-QUR’AN DI SEKOLAH MENENGAH ATAS TAKHASSUS AL-QUR’AN - Abdurrohman Al-Asy'ari (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2022)
This study seeks to reveal the management of the tahfidz application at SMA Takhassus Al-Qur'an, with qualitative research, using a descriptive explanatory case study strategy, analyzed using a comparative method. Earning research; Students who memorize the Al-Qur'an at SMA Takhassus Al-Qur'an are emphasized to start memorizing from the 114th, 113th, 112th chapters, placing Al-Baqarah's letter as the end of their memorization. To make it more optimal they are placed in dormitories and memorizing activities are integrated into the school curriculum. The method of memorizing the Al-Qur'an used by the institution. When viewed from the theory of learning to use two hemispheres of the brain, both emphasize optimizing the use of both hemispheres to memorize the Qur'an. This assessment is based on an analysis which states that there is harmony or suitability between the characteristics of the two methods used by each institution with the characteristics of the right and left brains. This suitability is shown by the presence of an unordered memorization model (right brain) and a time target (left brain)..